Peran KH. Abdul Ghofur dalam Pemilihan Umum Tahun 2014 di Wilayah Kecamatan Paciran Lamongan - Rohman, Ahmad Habibur (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2015)
Abstract: This paper discusses about the role of KH Abdul Ghofur within the general election in 2014 in Paciran-Lamongan. KH Abdul Ghofur was the one behind the winning effort of Gerindra party in Paciran. From the results of recapitulation of votes of the party in the general election in 2014, the Gerindra party got a very significant vote when compared with the number of votes in the general election in 2009. On the other hands, he was also the one behind one of legislative members of DPRD of Lamongan. Based on this, it can be concluded that the political role of KH Abdul Ghofur can be regarded as a very successful role in the winning effort of Gerindra party in Paciran. Therefore, the political role of the clerics cannot be disputed by the political elite and society in general. They can be used as a political role of the party either religion-based party or nationalist âbased party or even abangan-based party.Keywords: Role, cleric, victory, Gerindra, general election.